2016
DOI: 10.1007/s11606-016-3750-y
|View full text |Cite
|
Sign up to set email alerts
|

BMI Trajectories as a Harbinger of Pre-Diabetes or Underdiagnosed Diabetes: an 18-Year Retrospective Cohort Study in Taiwan

Abstract: BACKGROUND: Although prior studies have examined BMI trajectories in Western populations, little is known regarding how BMI trajectories in Asian populations vary between adults with and without diabetes. OBJECTIVE: To examine how BMI trajectories vary between those developing and not developing diabetes over 18 years in an Asian cohort. DESIGN: Multilevel modeling was used to depict levels and rates of change in BMI for up to 18 years for participants with and without self-reported physiciandiagnosed diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Previous studies, including the Bogalusa Heart Study, have indicated that glucose and insulin levels during adolescence are mediated by these factors, independent of adiposity [2325]. The findings from this and previous studies suggest that adolescence is a critical temporal window for BMI control to reduce the risk of adult hyperglycaemia [11, 1316, 2629]. …”
Section: Discussionsupporting
confidence: 49%
“…Previous studies, including the Bogalusa Heart Study, have indicated that glucose and insulin levels during adolescence are mediated by these factors, independent of adiposity [2325]. The findings from this and previous studies suggest that adolescence is a critical temporal window for BMI control to reduce the risk of adult hyperglycaemia [11, 1316, 2629]. …”
Section: Discussionsupporting
confidence: 49%
“…For those studies directly carried out with general adults, three of them only showed the developmental trajectories of BMI before the diagnosis of diabetes, without examining the relative risk of diabetes across distinct BMI trajectories. In another study consisting of 24,875 Australian adults, Peter et al .…”
Section: Discussionmentioning
confidence: 99%
“…For those studies directly carried out with general adults, three of them [34][35][36] only showed the developmental trajectories of BMI before the diagnosis of diabetes, without examining the relative risk of diabetes across distinct BMI trajectories. In another study consisting of 24,875 Australian adults, Peter et al 37 showed that the incidence of diabetes was different across distinct BMI trajectories; however, this study did not adjust for potential covariates in the regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Overaccumulation of ectopic lipids or hepatic fat causes serials of complex metabolic consequences [24] such as non-alcoholic fatty liver disease and insulin resistance, which will finally promote the development of diabetes. Recent studies have focused on diabetic correlations in longitudinal changes in multiple indices reflecting obesity and lipid metabolism, such as BMI [33, 34], visceral adiposity index [35], and lipids [36]. LAP combines waist measurements and fasting triglyceride (TG) levels, reflecting both the anatomic and physiological changes associated with lipid overaccumulation.…”
Section: Discussionmentioning
confidence: 99%